Removal of dissolved inorganic carbon from seawater for climate mitigation: potential marine ecosystem impacts - Hooper, Guy; Findlay, Helen S.; Bell, Thomas G.; Wilson, Rod W.; Halloran, Paul R. (Frontiers in Climate, 2025)
Electrochemical technology can be used to remove inorganic carbon from seawater and facilitate the removal of carbon dioxide (CO2) from the atmosphere. Electrochemical ‘Direct Ocean Carbon Capture and Storage’ (DOCCS) is a marine carbon dioxide removal (mCDR) method that removes atmospheric CO2 by releasing low-carbon seawater into the surface ocean, where it re-equilibrates with the atmosphere and stores atmospheric CO2. At the point of release, DOCCS discharge has low concentrations of dissolved inorganic carbon (DIC) and high pH, potentially causing unintended marine environmental impacts; however, its chemistry moves progressively towards that of ambient seawater as it dilutes and re-equilibrates with the atmosphere. To date, there are no published studies that investigate the impact of DOCCS discharge on marine ecosystems. Research from relevant analogues, where biological responses to low-DIC and/or high-pH seawater are investigated, provides some insight into potential DOCCS impacts. Despite this, significant evidence gaps remain. These evidence gaps are discussed alongside DOCCS-specific recommendations for future environmental impact research. Understanding the potential risks/benefits to marine ecosystems from discharge of low-DIC and high-pH seawater is critical to: (i) support licensing applications; (ii) develop any necessary mitigating actions; (iii) determine the net benefit of mCDR approaches; and (iv) stimulate informed public discourse about the acceptability of such approaches.